Measurement of ψ (2S) production as a function of charged-particle pseudorapidity density in pp collisions at √s = 13 TeV and p–Pb collisions at √sNN = 8.16 TeV with ALICE at the LHC - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Crkovská, Jana; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Kroesen, Martin; et al. (Journal of high energy physics, 2023)
Production of inclusive charmonia in pp collisions at center-of-mass energy of √s= 13 TeV and p-Pb collisions at center-of-mass energy per nucleon pair of √sNN = 8.16 TeV is studied as a function of charged-particle pseudorapidity density with ALICE. Ground and excited charmonium states (J/ψ, ψ(2S)) are measured from their dimuon decays in the interval of rapidity in the center-of-mass frame 2.5 < ycms < 4.0 for pp collisions, and 2.03 < ycms < 3.53 and −4.46 < ycms < −2.96 for p-Pb collisions. The charged-particle pseudorapidity density is measured around midrapidity (|η| < 1.0). In pp collisions, the measured charged-particle multiplicity extends to about six times the average value, while in p-Pb collisions at forward (backward) rapidity a multiplicity corresponding to about three (four) times the average is reached. The ψ(2S) yield increases with the charged-particle pseudorapidity density. The ratio of ψ(2S) over J/ψ yield does not show a significant multiplicity dependence in either colliding system, suggesting a similar behavior of J/ψ and ψ(2S) yields with respect to charged-particle pseudorapidity density. Results for the ψ(2S) yield and its ratio with respect to J/ψ agree with available model calculations.